GOOD CORPORATE GOVERNANCE, ANALYST COVERAGE, DAN TAHAPAN DAUR HIDUP TERHADAP KEBIJAKAN DIVIDEN - Werner R. Murhadi; Liliana Inggrit Wijaya (Journal of Management and Business, 2011)
This research objective is to observe the influences of good corporate governance, analyst coverage, company life cycle, investment opportunities set, size, and profitability towards the dividend policy. This study employs the corporate data from Indonesian Stock Exchange during 2005-2008 and weighted least square methods. The latest sample is 279 years of observation. The result shows that only life cycle stage of the company and its profitability are influential towards the dividend policy. The findings show that the relationship between the good corporate governance is consistent with the hypothesis but not significant.